The Role of Micrornas in Lipid Metabolism and their Probable Associations for Progress and Treatment of Atherosclerosis - Erum Rehman, Muhammad Shoaib, Aina Khurshid, Khadija Raziq, Mizhgan Ovais Khan, Nabila Sher Mohammad, Inam-U-Llah, Tanveer Tara, Sudhair Abbas Bangash (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Since plasma microRNAs (miRNAs) are stable in the circulatory system and are associated with a number of disorders, including coronary artery disease (CAD), the primary worldwide source of mortality and morbidity, they have been found in these conditions. Objective: This study aimed to define the functions of miRNAs in lipoprotein and lipid metabolism with a focus on the conceivable participation in the onset and development of atherosclerosis. Methods: This study was carried out at Hayatabad Medical Complex from November 2021 to March 2022. 85 patients (25 females and 60 males) diagnosed with the coronary angiography (CAG) were included because they were suspected of having CAD. Results: The results showed that patients with CAD exhibited down-regulated expression of miRNA-199a-5`, miRNA-135a-3`, miR17-5`, and miRNA-222-3` and up-regulated expression of miRNA-144-3`, miRNA-185-5`, miRNA-133a-5`, and miRNA-222-5` in comparison to the control group. Individuals with CAD and the group that didn't take statins both had significantly higher levels of miRNA-144-3` than the control group (p=0.040 and p=0.018, respectively). Both the statin and non-statin groups significantly outperformed the control group in terms of plasma level of miRNA-133a-5` (p=0.037 and p=0.011, respectively). Conclusion: The current study's findings revealed that CAD patients' expression levels of the miRNAs HSA miRNA-144-3`, HSA miRNA-222-5`, and HSA miRNA-133a-5` are significantly different from controls. Keywords: microRNAs, lipid metabolism, atherosclerosis, treatment